Vivências e experiências das docentes do ensino fundamental I acerca da prática pedagógica criativa em uma Escola Municipal de Goianésia-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The research "Experiences and practices of primary school teachers regarding creative pedagogical practice in a municipal school in Goianésia-GO" is linked to the research line "Education, School and Technologies". It is part of the Interdisciplinary Graduate Program in Education, Language, and Technologies (PPG-IELT) at the State University of Goiás (UEG). The study investigates to what extent primary school teachers understand creativity and show creative signs in their pedagogical practices. The general objective is to uncover the experiences and practices of primary school teachers at a municipal school in Goianésia-GO, aiming to understand how they perceive creativity and whether they demonstrate creative signs in their pedagogical practices. We believe that education driven by creative thinking is essential for developing new forms of learning that combine various types of knowledge and promote complex thinking. This empowers students to be active in their learning, aware of their autonomy, and their role in society.The adopted methodology is close to the phenomenological method, emphasizing the subjectivity of the participants. The qualitative approach aligns with the exploratory objectives. Procedures such as bibliographic research, document analysis, and field research were employed. Narrative interviews were used as a technical instrument for data collection, and the narratives were analyzed through hermeneutic interpretation, organized into units of meaning according to the participants' statements.The results showed that, although the teachers may not have a precise conceptual understanding of what constitutes a creative practice, they effectively applied creativity in the school context. The educators demonstrated a notable commitment to the comprehensive education of the students, covering both physical and mental aspects, and showed concern for the holistic development of the learners. However, the teachers' clear understanding of transdisciplinary and complex teacher training was identified as a limiting factor for deepening and expanding pedagogical practices aimed at comprehensive education of the learners. It is concluded that the school unit exhibits signs of creative practice, manifested by the educators' commitment to adopting approaches that go beyond mere content transmission and promote significant learning, preparing students to be protagonists of their learning and aware of their role in society.
Experiences and perceptions of elementary school teachers on creative pedagogica practices in a Municipal School in Goianésia-GO
Keywords: Docência - Ensino fundamental; Prática pedagógica criativa - Ensino fundamental; Ensino fundamental - Narrativas; Teaching - Elementary education; Creative pedagogical practice - Elementary education; Elementary education - Narratives; CIENCIAS HUMANAS::EDUCACAO